(untitled) (Annals of Medical Research, 2024)
Aim: Advances in the techniques and materials used in hypospadias surgery are aimed at improving cosmetic and functional results. In our study, we aimed to compare the impact of using Zaontz urethral stent (ZUS) on patient comfort in children undergoing hypospadias surgery, as opposed to feeding tubes. Materials and Methods: A total of 178 patients who underwent distal hypospadias surgery were included in the study. Snodgrass technique was performed routinely in all cases. In all cases, 6 Fr, 8 Fr and 10 Fr urethral stents were used depending on the surgical situation. Patients were divided into two groups according to the catheterization method. While in Group 1, catheterization was performed with a feeding tube, ZUS was used in Group 2. Demographic data of the patients were analyzed. In the postoperative period, the groups were compared in terms of patient comfort according to the Parents’ Postoperative Pain Measurement (PPPM) scale. This scale was evaluated three times a day during the hospitilation period. A score of at least 6 out of 15 was considered clinically significant pain. Results: Age, catheterization size, operation and hospitalization time were similar between the groups (p>0.05). PPPM score in Group 2 was observed as 3.25, significantly lower than Group 1 (p<0.001). Conclusion: As a result of our study, it was observed that ZUS would positively contribute to postoperative patient comfort in hypospadias repair.